2008
DOI: 10.1111/j.1744-6171.2008.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Latino Disparities in Child Mental Health Services

Abstract: The literature confirmed a pattern of underutilization of mental health services by Latino children, but did not completely address the reasons for the disparity. Suggested barriers were language and cultural issues. Gaps in the literature include a lack of agreement for definition of a mental health problem and the tools to identify these, insufficient studies into the barriers for Latino children in the access and utilization of mental health services, and cultural and language issues related to Latino resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…Finally, the first hypothesis also saw support in how academic achievement inversely related to externalizing behavior. While there is ample evidence of this inverse relationship among the general population (Bryant et al, 2003; Diego et al, 2003; Zimmermann et al, 2013), this study’s findings are in line with other Latino-specific studies demonstrating the negative association between academic achievement and externalizing behavior (C. Lopez et al, 2008; Vaughn et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Finally, the first hypothesis also saw support in how academic achievement inversely related to externalizing behavior. While there is ample evidence of this inverse relationship among the general population (Bryant et al, 2003; Diego et al, 2003; Zimmermann et al, 2013), this study’s findings are in line with other Latino-specific studies demonstrating the negative association between academic achievement and externalizing behavior (C. Lopez et al, 2008; Vaughn et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…As for the final hypothesis, only one significant indirect effect was found—academic achievement was found to mediate the association between the adolescent–teacher relationship and externalizing behavior. While studies analyzing this particular indirect pathway remained elusive, these findings are consistent with research that have found isolated occasions of links between the adolescent–teacher relationship and academic achievement (Rassiger, 2012; Roorda et al, 2011) and between academic achievement and externalizing behavior (C. Lopez et al, 2008; Vaughn et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations